DIGITAL DISCOURSE IN ENGLISH LANGUAGE TEACHING: EXPLORING MAN-MACHINE COLLABORATION MODELS THROUGH SYMBIOSIS THEORY - Xuemei, Wei (ppjbsip, 2025)
This study investigates the discursive dynamics of Man-Machine Collaboration (MMC) in English language teaching within the framework of symbiosis theory, aiming to explore how technological integration shapes pedagogical discourse in higher education settings across Asia. As digital tools become increasingly embedded in educational practices, understanding the evolving interaction between human educators and intelligent systems becomes essential. Drawing on a quantitative research design, data were collected from 653 participants, comprising 274 teachers and 379 students at a university in Asia. A structured survey was employed to assess the impact of MMC across four key dimensions: personalization, administrative efficiency, scalability, and adaptability to diverse learning needs. Findings reveal that personalization emerged as the most significant contributor to the effectiveness of the English teaching model (β = 0.40, p < 0.001), indicating the value of tailored instructional experiences in enhancing learner engagement. All other factors—administrative efficiency, scalability, and adaptability—also demonstrated statistically significant positive effects (p < 0.001), underscoring the multifaceted benefits of integrating AI-driven tools into pedagogical practices. These results suggest that the symbiotic relationship between human educators and machine-based systems has transformed traditional educational discourse into a more responsive, inclusive, and learner-centered format. The implications of this study are particularly relevant for discourse analysts and educators interested in the intersection of technology, language teaching, and cultural responsiveness in Asian contexts. By highlighting how digital mediation influences classroom communication and knowledge construction, this research contributes to broader discussions on the application of discourse analysis in contemporary educational settings. It also supports the use of digital platforms to enhance both the cognitive and affective dimensions of language instruction. Future research should examine the long-term evolution of such collaborative models across diverse linguistic, pedagogical, and institutional landscapes in Asia, with particular attention to qualitative dimensions of teacher-student interaction and discourse development.